Youth Politics of Scotland in the Context of the Problem of the Regionalization of the British Statehood - Pavel Alexandrovich Merkulov; Elena Nikolaevna Savinova (Управленческое консультирование)
In the article features of formation and essential features of youth policy in Scotland are considered in the context of the problem of regionalization of British statehood. The authors show that the Scottish youth policy in its development shares much of the English experience. Nevertheless, according to the authors, Scotland, in its approaches to the solution of most sociopolitical tasks (including work with young people), differs from England (meaningfully even more than sometimes can be seen in outward manifestations). In the article, the authors analyzed the differences that characterize the Scottish experience of youth policy, and which are the specific contribution of Scotland specifically to the tradition of working with young people. The authors’ conclusion is that the combination of youth work with adult education, as well as with the tasks of developing opportunities for socially vulnerable groups of the population, allowed to form their own national practice within the framework of the youth policy of Scotland. In addition, the authors conclude that the constant stability of the Scottish electoral system with its left bias and the steady political agenda on social inequality contributed to the specificity of Scotland’s youth policy. In the opinion of the authors, when the obvious disintegration of the system of working with young people began in England, the Scottish government supports all social institutions aimed at implementing the youth policy, which promotes the popularity of the ideas of Scotland’s national self-determination and independence in the ranks of young Scots.